2019
DOI: 10.1098/rspb.2019.1367
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of men's cooperation and social status in a small-scale society

Abstract: We propose that networks of cooperation and allocation of social status co-emerge in human groups. We substantiate this hypothesis with one of the first longitudinal studies of cooperation in a preindustrial society, spanning 8 years. Using longitudinal social network analysis of cooperation among men, we find large effects of kinship, reciprocity and transitivity in the nomination of cooperation partners over time. Independent of these effects, we show that (i) higher-status individuals gain more cooperation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 71 publications
(97 reference statements)
7
69
0
Order By: Relevance
“…Theory suggests that prestige is founded on a market-like exchange relationship (Henrich & Gil-White, 2001;Price & Van Vugt, 2014), buttressed by evidence that whenever an individual pays a cost to provide a public good, group members receiving the good confer prestige to the producer. In a similar vein, in a longitudinal study von Rueden, Redhead, O'Gorman, Kaplan, and Gurven (2019) found that men with highly prestigious reputations enjoyed an increased probability of receiving help from others, and were more likely chosen as future cooperation partners, highlighting how those who contribute to public goods reap social and material rewards. According to this logic, given that third-party punishment can signal an individual's cooperative intent, such forms of prosocial punishment may also similarly promote prestige.…”
Section: Why Punishing Can Promote One's Prestigementioning
confidence: 86%
See 2 more Smart Citations
“…Theory suggests that prestige is founded on a market-like exchange relationship (Henrich & Gil-White, 2001;Price & Van Vugt, 2014), buttressed by evidence that whenever an individual pays a cost to provide a public good, group members receiving the good confer prestige to the producer. In a similar vein, in a longitudinal study von Rueden, Redhead, O'Gorman, Kaplan, and Gurven (2019) found that men with highly prestigious reputations enjoyed an increased probability of receiving help from others, and were more likely chosen as future cooperation partners, highlighting how those who contribute to public goods reap social and material rewards. According to this logic, given that third-party punishment can signal an individual's cooperative intent, such forms of prosocial punishment may also similarly promote prestige.…”
Section: Why Punishing Can Promote One's Prestigementioning
confidence: 86%
“…By conferring aid and benefiting other group members through these prosocial means, individuals can increase and sustain both group-level cooperation, and their individual levels of prestige (Henrich et al, 2015;von Rueden et al, 2019).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…H ierarchical structure is a universal and pervasive aspect of human groups (1)(2)(3). Rank within a hierarchy-an individual's status within a group-defines access to fitness-relevant resources such as food, territory, mates, cooperative partners, influence, respect, and attention (4)(5)(6). Group members play an active role in determining who gains and loses relatively unchallenged access to valuable contested resources (7).…”
mentioning
confidence: 99%
“…Social structure resulting from kinship, friendship, and hierarchy among individuals is a hallmark of human society. Being a part of this structure is key for survival and reproduction 1,2 . Similar structures, albeit less complex, are also observed in other social species, including rodents 3 .…”
Section: Introductionmentioning
confidence: 99%